2022
DOI: 10.3892/etm.2022.11572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain Factor‑7® against motor deficit and oxidative stress in a mouse model of MPTP‑induced Parkinson's disease

Abstract: Oxidative stress is strongly implicated in the pathogenesis of Parkinson's disease (PD) through degeneration of dopaminergic neurons. The present study was designed to investigate the underlying mechanisms and therapeutic potential of Brain Factor-7 ® (BF-7 ® ), a natural compound in silkworm, in a mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). MPTP (20 mg/kg) was intraperitoneally injected into mice to cause symptoms of PD. Mice were orally administered BF-7 ® (a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Brain Factor-7® (BF-7®; a silk peptide) (>85%, pep-tide; alanine and tryptophan included as major ingredients) has been developed and produced by Famenity Co., Ltd. (Uiwang, Gyeonggi, Republic of Korea) and reported to show various biological activities [18][19][20]. For example, pretreatment with BF-7® reduces infarct volume in the forebrain following focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO) in rats and protects neuronal loss in the hippocampus of ischemic gerbil induced by tFI/R [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain Factor-7® (BF-7®; a silk peptide) (>85%, pep-tide; alanine and tryptophan included as major ingredients) has been developed and produced by Famenity Co., Ltd. (Uiwang, Gyeonggi, Republic of Korea) and reported to show various biological activities [18][19][20]. For example, pretreatment with BF-7® reduces infarct volume in the forebrain following focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO) in rats and protects neuronal loss in the hippocampus of ischemic gerbil induced by tFI/R [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, pretreatment with BF-7® reduces infarct volume in the forebrain following focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO) in rats and protects neuronal loss in the hippocampus of ischemic gerbil induced by tFI/R [20]. Furthermore, it has been demonstrated that treatment with BF-7® protects dopaminergic neurons in the substantia nigra and dopaminergic terminals in the striatum of a mouse model of Parkinson's disease induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [19].…”
Section: Introductionmentioning
confidence: 99%